Effect of escitalopram dose and treatment duration on CSF Aβ levels in healthy older adults: A controlled clinical trial. (10th November 2020) - Sheline, Yvette I.; Snider, B. Joy; Beer, Joanne C.; Seok, Darsol; Fagan, Anne M.; Suckow, Raymond F.; Lee, Jin-Moo; Waligorska, Teresa; Korecka, Magdalena; Aselcioglu, Irem; Morris, John C.; Shaw, Leslie M.; et al.
Abstract : Objective: To determine whether treatment with escitalopram compared with placebo would lower CSF β-amyloid 42 (Aβ42 ) levels. Rationale: Serotonin signaling suppresses Aβ42 in animal models of Alzheimer disease (AD) and young healthy humans. In a prospective study in older adults, we examined dose and treatment duration effects of escitalopram. Methods: Using lumbar punctures to sample CSF levels before and after a course of escitalopram treatment, cognitively normal older adults (n = 114) were assigned to placebo, 20 mg escitalopram × 2 weeks, 20 mg escitalopram × 8 weeks, or 30 mg escitalopram × 8 weeks; CSF sampled pretreatment and posttreatment and within-subject percent change in Aβ42 was used as the primary outcome in subsequent analyses. Results: An overall 9.4% greater reduction in CSF Aβ42 was found in escitalopram-treated compared with placebo-treated groups ( p < 0.001, 95% confidence interval [CI] 4.9%–14.2%, d = 0.81). Positive baseline Aβ status (CSF Aβ42 levels <250 pg/mL) was associated with smaller Aβ42 reduction ( p = 0.006, 95% CI −16.7% to 0.5%, d = −0.52) compared with negative baseline amyloid status (CSF Aβ42 levels >250 pg/mL). Conclusions: Short-term longitudinal doses of escitalopram decreased CSF Aβ42 in cognitively normal older adults, the target group for AD prevention. Clinicaltrials.gov identifier: NCT02161458. Classification of evidence: This study provides Class II evidence that for cognitively normal older adults, escitalopram decreases CSF Aβ42 .